(untitled) (Research, Society and Development, 2023)
In short, most of the mineral waters consumed by human beings are captured through natural springs or artesian wells. The mineral water industrialization process happens when they are transferred to reservoirs through pumps with PVC (polyvinyl chloride) or stainless steel tubes so that in this process contamination of the collected water is prevented. The production of mineral water in the Metropolitan Region of Recife has been growing in recent years and, economically, it is one of the main mining activities in the region. The State of Pernambuco has 45 active mineral water complexes, of which 27 are found in the Metropolitan Region of Recife. It is important to investigate and analyze the quality of water for human consumption, since it is through the consumption of these water sources that various diseases are proliferated. The aim of this study was to perform the counting of heterotrophic bacteria in samples of mineral water from different brands marketed in the metropolitan region of Recife-PE, using the “Pour–plate” method. According to the percentage that presents in the first period 85.71% (in compliance) and 14.28% (not in compliance). In the second period, 57.14% are (compliant) and 42.85% (non-compliant). That is, in the second period (June to August) /2015, a high percentage of waters were detected that had their departures from samples that are not in compliance due to the presence of microbiological bacteria in the analyzed mineral water samples. Regarding the periods, it is possible to observe that in the period from June to August the microbiological analyzes had a higher percentage of rejection in relation to the period (January to April). The work is justified by the importance of water for the survival and maintenance of life. In addition to being an alert for more intense monitoring of the potability of water by the responsible body, it is in fact important to investigate the quality of this water that is being destined for consumption from its bottling process to the final destination of the water (our residences).